Mountain and cold weather: critical capability for the 21st century. - Pierce, Scott W. (Fort Leavenworth, KS : US Army Command and General Staff College, 2008)
This monograph posits that military operations in high mountains or intense cold require forces with specialized organization, training and equipment. The author compares characteristics of military operations in mountains and cold weather, and defines the mountain/cold weather (MCW) environment. The author describes the effect of the MCW environment on each of the six warfighting functions. To illustrate the effects of the MCW environment on military operations, the author briefly reviews the cold weather Suomussalmi campaign, during the Soviet-Finnish Winter War, and the high mountain Kargil campaign, in the disputed state of Jammu and Kashmir, one of many bloody confrontations between India and Pakistan. The author summarizes and briefly describes those regions that hold both strategic importance for the United States and that are characterized by high mountains or cold climates. These regions are: Central and South Asia, the Caucasus, Iran, the Andes, and the Arctic. The author then catalogs current U.S. military MCW warfighting (MCWW) capabilities, concluding that the capacity currently resident within the U.S. Armed Forces is insufficient. Recognizing that the development of a dedicated specialized force is an inefficient and unrealistic goal for the U.S. military, the author recommends a "hedging strategy" to provide a minimally acceptable "off-the-shelf" capability to support U.S. regional combatant commanders. This hedging strategy includes the designation of a Department of Defense executive agent, a high level programs office to direct and coordinate doctrine, training and procurement, and the establishment of modern training centers. Finally, the author advocates organizing, training and equipping specialized units, designed to provide supported general purpose forces with MCW-specific expertise and equipment.